Digging into primary financial market: The issues of primary financial market issuance and investigations from the perspective of blockchain - Liu, Ji; Xu, Zheng; Zhang, Yanmei; Dai, Wei; Wu, Hao; Chen, Shiping (Frontiers in Blockchain, 2022)
With the characteristics of anonymity, trust, tamper-proof, etc., blockchain technology can effectively solve some problems faced by the financial market, such as trust issues and information asymmetry issues. To deeply understand the application scenarios of blockchain in the financial market, the issue of securities issuance and trading in the primary market is a problem that must be studied clearly. We conducted an empirical study to investigate the main difficulties faced by primary market participants in their business practices and the potential challenges of the deepening application of blockchain technology in the primary market. We adopted a hybrid method combining interviews (qualitative methods) and surveys (quantitative methods) to conduct this research in two stages. In the first stage, we interview 15 major primary market participants with different backgrounds and expertise. In the second phase, we conducted a verification survey of 54 primary market practitioners to confirm various insights from the interviews, including challenges and desired improvements. Our interviews and survey results revealed several significant challenges facing blockchain applications in the primary market: complex due diligence, mismatch, and difficult monitoring. The research shows that primary market participants have a positive attitude towards the application of blockchain technology to the primary market and are ready to adopt blockchain technology to solve some of the current issues.